2017
DOI: 10.1002/jcla.22205
|View full text |Cite
|
Sign up to set email alerts
|

Combination of change in hematological parameters with exercise stress test to predict coronary artery disease

Abstract: Objective: Treadmill exercise stress testing for identifying patients with a higher likelihood of coronary artery disease (CAD) before elective coronary angiography is recommended in the current guidelines. In this study, we aimed to evaluate the changes in the hematological parameters before and after exercise stress test in relation with the presence of CAD. Methods:A total of 113 patients with chest pain who underwent treadmill exercise testing and coronary angiography were included in this study. Conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…These consisted of 76,002 participants from 11 case–control, 9 cohort, and 18 cross-sectional studies. There were 16, 6, 10, and 5 studies that, respectively, reported stable CAD [ 10 17 , 19 – 26 ], ACS [ 27 – 32 ], stroke [ 33 42 ], and composite CVD outcomes [ 43 47 ]. One study [ 18 ] reported both CAD and ACS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These consisted of 76,002 participants from 11 case–control, 9 cohort, and 18 cross-sectional studies. There were 16, 6, 10, and 5 studies that, respectively, reported stable CAD [ 10 17 , 19 – 26 ], ACS [ 27 – 32 ], stroke [ 33 42 ], and composite CVD outcomes [ 43 47 ]. One study [ 18 ] reported both CAD and ACS.…”
Section: Resultsmentioning
confidence: 99%
“…Among 17 studies of 8,988 subjects, 4 studies [ 14 , 16 , 20 , 23 ] reported ORs of high versus low NLR, 8 studies [ 10 12 , 17 , 19 , 21 , 22 , 26 ] reported mean differences of NLR between CAD and non-CAD patients, and 5 studies [ 13 , 15 , 18 , 24 , 25 ] reported both.…”
Section: Resultsmentioning
confidence: 99%
“…Of the five studies investigating the impact of acute exercise on the PLR, three showed increased values post-exercise, indicating an inflammatory response (see Table 2 ). Considering exercise-induced thrombocytosis instead of neutrophilia, PLR might, therefore, serve as a useful alternative or addition to NLR, as indicated by increases in both markers in response to acute exercise in healthy (Wahl et al 2020 ) and diseased populations (Korkmaz et al 2018 ). Interestingly, PLR values were altered more profoundly by high intensity exercise modalities with values around twice higher than at rest and absolute values over 200 (Wahl et al 2020 ).…”
Section: Current State Of Knowledge—nlr Plr and Sii In Exercise Physiologymentioning
confidence: 99%
“…It has been also suggested that the NLR can provide a good measure of exercise stress and subsequent recovery since in the hours following recovery from exercise the blood neutrophil count continues to increase and the blood lymphocyte count decreases 7 . NLR has been reported to increase significantly following exercise stress test with subjects who had coronary artery disease, whereas in subjects with a positive exercise test outcome this increase has been even more significant 8 . The NLR usually returns to normal within six to nine hours after exercise, but where the exercise has been particularly prolonged and stressful, the NLR may still be elevated at 24 hours post-exercise 9 .…”
Section: Discussionmentioning
confidence: 43%